2020
DOI: 10.1590/0100-3984.2019.0075
|View full text |Cite
|
Sign up to set email alerts
|

An initial investigation of serum cytokine levels in patients with gadolinium retention

Abstract: Objective: To determine whether individuals with proposed gadolinium deposition disease (GDD) have elevated serum levels of pro-inflammatory and pro-fibrotic cytokines, and whether specific cytokines are correlated with certain symptoms. Materials and Methods: Twenty-four participants recruited between May 2016 and June 2017 met GDD diagnostic criteria. The 64 control subjects provided serum samples before prophylactic flu vaccination. Serum cytokine levels were obtained with Luminex serum cytokine assay usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 30 publications
1
31
1
Order By: Relevance
“…Our opinion is that the authors of that paper were reporting a case of GDD and not fibromyalgia. Another recent study showed that cytokine profiles determined from serum samples differed between individuals with GDD and those in a group of age-and gender-matched controls (21) .…”
Section: Discussionmentioning
confidence: 98%
“…Our opinion is that the authors of that paper were reporting a case of GDD and not fibromyalgia. Another recent study showed that cytokine profiles determined from serum samples differed between individuals with GDD and those in a group of age-and gender-matched controls (21) .…”
Section: Discussionmentioning
confidence: 98%
“…Reduced levels suggest that retained Gd lowers mitochondrial resistance to adverse stressors, including possibly the increased levels of pro-inflammatory cytokines reported in GDD (Maecker et al, 2020). Again, confirmation in unextracted NDEVs and intact mitochondria is required.…”
Section: Discussionmentioning
confidence: 99%
“…Low GdCl 3 and GBCA concentrations induced cytokine release in mouse macrophages, including TNF-α, IL-6, and IL-10, increased ROS, and suppressed Ψ m [4]. As our cohort was a subset of GDD patients with higher peripheral TNF-α and IL-6 in association with new onset frequent headaches and neuropathic pain [23], the consistently elevated 5-methylthioadenosine (MTA), decreased adenosine, and altered arachidonic acid (AA) we observed may be clinically meaningful. MTA is an increasingly appreciated metabolic regulator of susceptibility and severity in sepsis; high plasma levels correlate strongly and positively with IL-6 and IL-8, and weakly with TNF-α, and signal a worse prognosis due to hyperinflammation [49].…”
Section: Discussionmentioning
confidence: 79%
“…The shortest time from symptom onset to blood draw was 70 days (mean = 330 days; median = 248 days), suggesting an ongoing and potentially progressive process in some cases. Congruent with reports that GDD symptom chronicity is independent of cumulative GBCA dose and retention [23,28], no association was detected between urinary Gd and total or MD symptom scores (r = −0.12, p = 0.67; r = −0.19, p = 0.50), nor did severity correlate with days between the symptom-related MRI and symptom assessment (total: r = −0.06, p = 0.83; MD: r = −0.01, p = 0.97). However, a moderately significant association was seen between number of lifetime MRIs and MD symptom score (r = 0.53, p = 0.04), with a near-significant trend for total symptom score (r = 0.47, p = 0.08).…”
Section: Participant Clinical Characteristicsmentioning
confidence: 81%
See 1 more Smart Citation